Bio-efficacy of fungicides and bio control agents against root rot of soybean incited by Rhizoctonia solani: Bio-efficacy of fungicides and bio control agents against root rot of soybean incited by Rhizoctonia solani - PUNAM KASHYAP; S N SINGH; M SURYA PRAKASH REDDY; JHUMISHREE MEHER (Journal of Oilseeds Research, 2020)
Bioagents, fungicides and their combinations were tested under net house conditions to know their efficacy in controlling root rot of soybean. The parameters recorded included percent germination, dry weight, vigour index and vigour index mass. Seed dressing with Aazoxystrobin + T. viride showed highest significant effect on germination per cent and dry weight. However, seed dressing with T. harzianum were significant on fresh weight and vigour index.